2020
DOI: 10.22541/au.160510683.36272688/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in Childhood: Transmission, Clinical Presentation, Complications and Risk Factors

Abstract: Children less than 18 years of age account for an estimated 500,000 to 1.5 million global SARS-CoV-2 cases. Lower prevalence of COVID-19 among children, in addition to higher numbers of mild and asymptomatic cases, continues to provide challenges in determining appropriate prevention and treatment courses. Here, we summarize the current evidence on the transmission, clinical presentation, complications and risk factors in regards to SARS-CoV-2 in children and highlight crucial gaps in knowledge going forward. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…This study revealed more than half patients were household transmission. This finding is consistent with several observational studies [22,37–40] and literature reviews [41] which pointed out children are more likely to contract virus from adult household members. Moreover, the clinical features of the disease were mild in this study and almost one-half patients were asymptomatic.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed more than half patients were household transmission. This finding is consistent with several observational studies [22,37–40] and literature reviews [41] which pointed out children are more likely to contract virus from adult household members. Moreover, the clinical features of the disease were mild in this study and almost one-half patients were asymptomatic.…”
Section: Discussionsupporting
confidence: 93%
“…While obesity has been consistently associated with risk of severe disease, findings regarding other comorbidities have been inconsistent. 20 Kompaniyetes et al, for example, did not include a category of chronic lung disease and did not find an association between asthma or neurodevelopmental disorders and severe illness. 9 As for the risk of complications from the vaccine, information about children less than 12 years is forthcoming.…”
Section: Timothy K Knilans a Pediatric Cardiologist And Chair Of A Pharmacy And Therapeutics Committee Commentsmentioning
confidence: 99%
“…As a proof-of-concept study, this work also did not take account of all variables likely to affect household transmission and worked under certain hypotheses concerning family size and constitution. For example, distribution of offspring age was not accounted for, although younger children are less likely to transmit COVID-19 [19] while older children are more likely to lose contact with their fathers, which would reduce OHL. In the absence of available data, we were not able to account for variation in the amount of time that a child spent with each parent, or the frequency of movement between households.…”
Section: Limitationsmentioning
confidence: 99%